The Effect of William Flexion Exercise on Reducing Pain Intensity For Elderly with Low Back Pain - Amila Amila; Henny Syapitri; Evarina Sembiring (Alta Dharma Publisher, 2021)
The elderly are a group of the population that has the potential to become vulnerable communities. In the elderly, the aging process can cause various physical problems. One of the issues that often arise in the elderly is low back pain (NPB). The purpose of this study is to evaluate the effect of the William Flexion Exercise on reducing the pain intensity for elderly with low back pain at Hisosu Binjai Resident Home, Indonesia. The research design is quasi-experimental with the pre and post-test control group approach in 2017. This study's sample consisted of 28 people in the intervention group and 28 people in the control group. The sampling technique utilized consecutive sampling. This study used The Pain Numerical Rating Scale to evaluate the level of pain intensity perceived by the patient. The data were analyzed by dependent and independent t-test with significance ? < 0.05. The dependent t-test found a significant difference in the low back pain before and after the intervention group intervention (p-value =0.000). In contrast, there is no significant difference in the control group (p-value = 0.081). The result of the independent t-test found that there are significant differences in the low back pain between the intervention group and the control group. This study concludes that William's flexion exercise provided benefits to most of the participants in this study. Thus, it may be an effective technique to reduce pain intensity and increase the range of motions